2014
DOI: 10.1017/s1368980014001633
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tools used to measure calcium and/or dairy consumption in adults

Abstract: Objective: To identify and critique tools for the assessment of Ca and/or dairy intake in adults, in order to ascertain the most accurate and reliable tools available. Design: A systematic review of the literature was conducted using defined inclusion and exclusion criteria. Articles reporting on originally developed tools or testing the reliability or validity of existing tools that measure Ca and/or dairy intake in adults were included. Author-defined criteria for reporting reliability and validity propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Nevertheless, the authors of the mentioned report suggest that when selecting the method of evaluation, it makes sense to take into account the type, size, age, sex and physiological condition of a population. It may then be worthwhile to classify nutrition evaluation methods in the context of various studied groups [26]. A Croatian study of 333 postmenopausal women has demonstrated that FFQ may not be suitable for determination of either low, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the authors of the mentioned report suggest that when selecting the method of evaluation, it makes sense to take into account the type, size, age, sex and physiological condition of a population. It may then be worthwhile to classify nutrition evaluation methods in the context of various studied groups [26]. A Croatian study of 333 postmenopausal women has demonstrated that FFQ may not be suitable for determination of either low, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,23,[33][34][35][36][37] A team of seven (dairy) nutrition professionals critically reviewed the items to check for relevance, understandability and face validity in the South African context, since elicitation is a first step in appropriately applying the TPB. 20 The questionnaire was tested prior to administration.…”
Section: Methodsmentioning
confidence: 99%
“…Setting and meeting structure-Pre-meeting materials were updated between Phases 1 and 2. Prior to arriving, participants were provided with instructions and guidelines (see supplemental materials), as well as a collection of systematic reviews and meta-analyses (Alexander et al, 2016;Bordoni et al, 2017;Crichton, Bryan, Buckley, & Murphy, 2011;de Goede, Geleijnse, Ding, & Soedamah-Muthu, 2015;de Goede, Soedamah-Muthu, Pan, Gijsbers, & Geleijnse, 2016;Ding et al, 2017;Dumas et al, 2017;Geng, Qi, & Huang, 2017;Gibson, Makrides, Smithers, Voevodin, & Sinclair, 2009;Labonte, Couture, Richard, Desroches, & Lamarche, 2013;Larsson, Crippa, Orsini, Wolk, & Michaelsson, 2015;Liang, Zhou, Kwame Amakye, Su, & Zhang, 2016;Magarey, Baulderstone, Yaxley, Markow, & Miller, 2015;McGrane et al, 2011;Mente, de Koning, Shannon, & Anand, 2009;Mullie, Pizot, & Autier, 2016;Ndanuko, Tapsell, Charlton, Neale, & Batterham, 2016;Pasin and Comerford, 2015;Pimpin, Wu, Haskelberg, Del Gobbo, & Mozaffarian, 2016;Ralston, Lee, Truby, Palermo, & Walker, 2012;Schwab et al, 2014;Soedamah-Muthu, Verberne, Ding, Engberink, & Geleijnse, 2012;Sun and Buys, 2015;Thorning et al, 2017;Wu and Sun, 2017). These reviews included RCTs, but were not necessarily exclusively RCTs, and may have only reviewed (not meta-analyzed) the studies.…”
Section: Phase 2: Final Dialogue Mapping Sessionmentioning
confidence: 99%
“…Notably, most large-scale analyses use self-reported intake data, the strengths and limitations of which have been described thoroughly elsewhere [c.f., (Dhurandhar et al, 2015;Subar et al, 2015)]. In addition to the typical limitations of self-report, specific concerns were discussed about dairy foods (Magarey, et al, 2015). For instance, some questionnaires have not distinguished amongst full-, reduced-, or non-fat dairy (Mente, et al, 2009).…”
Section: Individual Factors-with the Increasing Focus On 'Precision' Or 'Individualized'mentioning
confidence: 99%